Mathematics module based on STEAM and Quranic approach: A study for student’s perception - Muzakkir; Zulnaidi, Hutkemri; Abd Rauf , Rose Amnah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Monotonous mathematics learning focusing on textbooks only will make students bored and feel that studying mathematics is useless. Using attractive and meaningful approaches, like STEAM and Quranic approaches, is strongly motivated by the need to avoid tedious drilling for students in learning mathematics. This study aims to assess students' perceptions of the development of mathematics modules using science, technology, engineering, and art (STEAM) and AL-Quran approaches. The research approach employed in this research is embedded in mixed methods. Quantitative data was examined using percentages, while qualitative data were transcribed and then developed into codes, categories, and themes. The study recruited 146 Pidie senior high school students in the natural science stream, and five individuals were selected for one-to-one semi-structured interviews. The results of this study show that students have a negative experience in learning mathematics. However, they have a significant interest in integrated math learning with Quranic and STEAM approaches. Furthermore, they believe the modules are one learning medium ideal for mathematics. Finally, based on this study, mathematics teachers should be able to develop learning modules that can integrate STEAM approaches and the understanding of the Quran for senior high school students.